(untitled) (Vietnam Journal of Agriculture and Environment, 2024)
Evaluation of productive silkworm breeds is the first important component in the development of sericulture. The present study was conducted to assess larvae and cocoon characteristics of 22 bivoltine silkworm races under standard and high tempearature and humidity conditions. Under the standard condition, the races with high reelibility > 80%, rendital < 7 kg, EI > 50 were TQ10 (59.51), IN6 (58.66), IN3 (57.14), IN2 (58.66), HQ4 (53.86), TQ9 (53.49), TQ5 (53.45), TQ3 (52.56), TQ7 (51.64) and TQ1 (50.08). In high temparature and humidity conditon, the silkworm races with high survival > 80% were VN2, TQ6, VN7, TQ1, TQ2 and TQ10. EI>50 were recorded in HQ4 (58.32), TQ7 (56.26), TQ10 (56.88), TQ9 (56.26), TQ6 (55.39), TQ3 (55.10), IN6 (54.79), TQ5 (54.78) and IN3 (54.29). Therefore, the identified races can serve as valuable resource materials for breeding silkworms programs tailored to challenging environmental conditions.